Characteristics Of Corn Drying Using Small Scale Dome Type Dryer - Meylan Kowimbin; Ireine A. Longdong; Dedie Tooy (Sam Ratulangi University, 2023)
This study aims to measure drying temperature, relative humidity (RH), moisture content, and drying rate versus time in small-scale dome-type dryers. The results of research on drying corn using a small-scale dome-type dryer The average air temperature on the first day of the experiment was 43.7â°C, and on the second day was 42.8â°C. First 2 days experiment 34â°C, the second day 37.4â°C third day 42.1â°C. The average air humidity on the first 1-day experiment was 38%, and the second day was 41%. On the first 2 days of the experiment, the average air humidity was 38%, on the second day was 38%, and on the third day was 36%. The water content during the drying process of corn without husks and corn husks in experiment 1 averaged the initial moisture content of corn without husks at 22.7% and corn husks at 22.5%. Experiment 2 averaged the initial moisture content of corn without husks at 29.7% and corn husks at 30.5%. Experiment 1 with a drying time of 16 hours and experiment 2 20 hours with an average final content of 13-14%. The average drying rate in experiment 1 of corn without husk was 1.46%/hour, corn with husk was 1.15%/hour, and in the second experiment the average drying rate of corn without husk was 1.08%/hour, corn with husk was 1.00%/hour. Keywords: Â Corn Drying, Small Scale Dome. Abstrak Penelitian ini bertujuan untuk mengukur suhu pengeringan, kelembaban relative (RH), kadar air, serta laju pengeringan terhadap waktu pada alat pengering tipe dome skala kecil. Hasil dari penelitian pengeringan jagung menggunakan alat pengering tipe dome skala kecil Suhu udara alat rata-rata pada percobaan 1 hari pertama 43,7â°C, hari kedua 42,8â°C. Percobaan 2 hari pertama 34â°C, hari kedua 37,4â°C hari ketiga 42,1â°C. Kelembaban udara rata-rata pada percobaan 1 hari pertama 38%, hari kedua 41%. Percobaan 2 hari pertama kelembaban udara rata-rata 38%, hari kedua 38%, dan hari ketiga 36%. Kadar air selama prosesÂ pengeringan jagung tanpa klobot dan jagung klobot percobaan 1 rata-rata kadar air awal jagung tanpa klobot 22,7% dan jagung klobot 22.5%. Percobaan 2 rata-rata kadar air awal jagung tanpa klobot 29,7% dan jagung klobot 30,5%. Percobaan 1 dengan lama pengeringan 16 jam dan percobaan 2 20 jam dengan rata-rata kadar akhir 13-14%. Laju pengeringan rata-rata pada percobaan 1 jagung tanpa klobot sebesar 1,46%/jam, jagung klobot 1,15%/jam, dan percobaan kedua rata-rata laju pengeringan jagung tanpa klobot yaitu 1,08%/jam, jagung klobot yaitu 1,00%/jam. Kata Kunci : PengeringanÂ Jagung,Â Dome Skala Kecil